Climate change and its impacts on hydrological regimes over the Bengal delta - M.H. Ali; P. Biswas; S.M.Q. Hassan; M.A. Islam (Results in Engineering)
Global warming and climate change are causing temperature to rise, which is having an impact on hydrology and water resources. Simulating the potential impacts of future climate change on hydrologic regimes provides opportunities to improve the climate change resilience of agricultural and other water-related systems. Bangladesh, the largest delta of the world, is confronted with substantial challenges from climate change risks and the depletion of the aquifer's groundwater supply. This study quantifies the impacts of climate change on hydrologic regimes (recharge, runoff, ET0, ET). Future climatic data projected by the CMIP6 GCM (ACCESS) under two shared socioeconomic pathways (SSPs) SSP2–4.5 (moderate emission scenario) and SSP5–8.5 (high emission scenario) were used. The projected climatic data demonstrate variations in rainfall and temperature across the country and as well as in the upcoming decades (2041–50 to 2091–2100). In most situations, there is a discernible and significant upward trend in the predicted future temperature. Under SSP4.5, the yearly rainfall deviated from -14 to 58 %, January temperature from -3.7 to 31.4 %, April temperature from 2 to 17.3 %, ET0 from 1.8 to 9.8 %, PET from 1.9 to 9.6 %, runoff from -25 to 144 %, and groundwater recharge from -33.1 to 44.7 %. Under SSP8.5, the magnitude of variation of the parameters is generally higher than those of SSP4.5. The dry winter period is getting drier and falls under semi-arid to hyper-arid categories according to the drought indices. It is anticipated that over the 2040–2070 timeframe, the Rajshahi region would receive the least quantity of precipitation overall. Predominantly in response to the amount and pattern of rainfall, surface runoff and groundwater recharge exhibit rising or falling behavior. Both scenarios predict rising temperatures in all locations throughout the cold (January) and hot (April) months throughout the 21st century, with higher increasing trends under SSP8.5. The rising temperature raises concerns about crop heat stress and probable yield loss. Decreasing rainfall and groundwater recharge and increasing evapotranspiration may underscore the sustainability of water supply. Therefore, it is essential for policymakers to take some appropriate measures and strategies in advance to strengthen the resilience to climate change.